Predicting intestinal effective permeability of different transport mechanisms: Comparing ex vivo porcine and in vitro dialysis models. (February 2023) - Li, Yiwen; Park, Hea Jin; Xiu, Haning; Akoh, Casimir C.; Kong, Fanbin
Abstract: Intestinal effective permeability ( P eff ) is among the most critical parameters that determine the bioavailability of nutrients. Rats have been widely used to estimate the P eff of bioactive compounds. However, distinct physiological differences between rats and humans hamper accurate prediction of the P eff . Herein we presented an ex vivo porcine intestinal model to predict the P eff of two model nutrients which involve both active transport (d -glucose) and passive transport (gallic acid). The results were compared with an in vitro dialysis model which has gained increasing interest in simulating intestinal absorption. The results indicated that the ex vivo porcine model maintained the integrity of the villus epithelium and closely predicted the human P eff of the two compounds. The P eff values of d -glucose obtained from the porcine model (2.37 × 10 −4  cm/s) and the dialysis model with 8000 Da dialysis membrane (2.16 × 10 −4  cm/s) were comparable to that obtained from healthy volunteers, and higher than that from Caco-2 model, rat in situ and ex vivo models. The P eff obtained from the in vitro dialysis model was affected by the molecular weight cut-off (MWCO). Specifically, the human P eff was closely predicted when 8000 MWCO was selected. The P eff values of gallic acid were 1.70 × 10 −4  cm/s for the porcine model, 1.35 × 10 −4  cm/s for the dialysis model with 8000 Da MWCO, and 1.33 × 10 −4  cm/s for the 1000 Da MWCO, respectively. These values were consistent with those reported in the rat in situ and Ussing chamber models, regardless of intestinal resources. Both models exhibited potential for use in intestinal permeability assessment of nutrients and can serve as a screening tool for nutrient bioavailability and absorption. Highlights: An ex vivo porcine model and an in vitro dialysis model were developed to estimate the intestinal permeability ( P eff ). The ex vivo porcine model closely predicted the human P eff of d -glucose (active transported) and gallic acid (passive transported). The in vitro dialysis model closely predicted the P eff of gallic acid, but the P eff of d -glucose was dependent on the MWCO of the dialysis membrane. Both models exhibited potential for use in intestinal permeability assessment of nutrients.